Pelatihan dan Pendampingan Penyusunan Tugas Akhir menggunakan Berbagai Tools AI - Bakri, Rizal; Hasbiyadi, Hasbiyadi; Astuti, Niken Probondani (Ilin Institute, 2024)
This activity aims to develop and implement a training and mentoring program for students to prepare their final assignments by utilizing various artificial intelligence (AI) tools. The AI tools used include ChatGPT for data analysis, Perplexity for compiling text, Mendeley for references, Spinner.id for paraphrasing, and Turnitin for checking plagiarism. Implementation methods include offline workshops and individual consultation sessions. Students are introduced to various AI tools through intensive training sessions that include compaction of usage, practical exercises, and direct assistance in applying these tools to their final assignments. The results of the activities showed a significant increase in the quality of students' final assignments. The use of AI tools facilitates the processes of data analysis, text preparation, reference management, content paraphrasing, and plagiarism checking. Students can complete final assignments more efficiently and reduce stress levels. Therefore, the use of AI in preparing final assignments offers an effective solution to overcome various obstacles faced by students. This training and mentoring program is highly recommended for acceptance by higher education institutions to support students in completing their final assignments with better quality.